E-learning and its influence on Teachers’ Professional Development in Zimbabwe - Tawanda Shonhiwa (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
This paper sought to gain insight into e-learning and its influence on teachers’ professional development in Zimbabwe. The methodological lens used in interrogating this issue comprised of the interpretive paradigm and qualitative approach. As sources of data fifty participants were purposively selected. Data was generated the through literature method, focus group discussion and in-depth interviews. Analysis of the sourced data was narrative in nature buttressed by emerging themes. Findings acknowledged the existence of policies enabled the introduction of e-learning in teacher training institutions. It was further revealed that the implementation of the new framework that enabled the inclusion of e-learning in teachers’ training courses. From the discussion it can be concluded that e-learning is indeed of much attention in various sectors of the education system to enable professional growth. The study recommended the provision of e-learning professional development and support to all college departments to ensure its successful integration into daily teacher training routines.